Tuberculous dactylitis (spina ventosa) with concomitant ipsilateral axillary scrofuloderma in an immunocompetent child: A rare presentation of skeletal tuberculosis - Bhaskar (Medknow Publications & Media Pvt Ltd, 2013)
Tuberculous dactylitis is a distinctly uncommon, yet well recognized form of tuberculosis involving the small bones of the hand or foot. It occurs in young children in endemic areas under 5 years of age. Tuberculosis of the short tubular bones like phalanges, metacarpals or metatarsals is quite uncommon beyond 6 years of age, once the epiphyseal centers are well established. The radiographic features of cystic expansion have led to the name “Spina Ventosa” for tuberculous dactylitis of the short bones. Scrofuloderma is a mycobacterial infection affecting children and young adults, representing direct extension of tuberculosis into the skin from underlying structures e.g. lymph nodes. An 8-year-old malnourished girl had multiple axillary ulcers with lymphadenopathy. Tuberculous dactylitis with ipsilateral axillary scrofuloderma was suspected on clinical and radiological grounds. The suspicion was confirmed by histology and bacteriology. The patient responded to antitubercular drugs with progressive healing of the lesions without surgery. Concomitant presence of these dual lesions suggesting active disseminated tuberculosis in immune-competent child over 6 years is very rare and hardly reported.